2017
DOI: 10.1001/jamainternmed.2016.7031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Goals of Care Intervention for Advanced Dementia

Abstract: In advanced dementia, goals of care decisions are challenging and medical care is often more intensive than desired.OBJECTIVE To test a goals of care (GOC) decision aid intervention to improve quality of communication and palliative care for nursing home residents with advanced dementia. DESIGN, SETTING, AND PARTICIPANTSA single-blind cluster randomized clinical trial, including 302 residents with advanced dementia and their family decision makers in 22 nursing homes.INTERVENTIONS A GOC video decision aid plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
289
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 224 publications
(309 citation statements)
references
References 35 publications
9
289
1
3
Order By: Relevance
“…As in other advanced dementia studies involving primary data collection, 2,4,9 there was a high proxy refusal rate. Although preferences may have differed between proxies who did and did not participate, this possibility is less likely to have impacted the analyses examining factors associated with a preference for comfort care.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…As in other advanced dementia studies involving primary data collection, 2,4,9 there was a high proxy refusal rate. Although preferences may have differed between proxies who did and did not participate, this possibility is less likely to have impacted the analyses examining factors associated with a preference for comfort care.…”
Section: Discussionmentioning
confidence: 64%
“…2,4 The present study suggests that embedded in that 95% are approximately one-third of proxies who would opt for basic medical care, which may include potentially curative treatments (e.g., antimicrobials) and hospitalization. The proportion of proxies strictly choosing comfort care (62%) was similar to that found in a comparable cohort when options were presented as three goals of care; “prolonging life, supporting function, or improving comfort.” 9 As in earlier research, 2,4,5,9 only a small proportion of proxies felt residents with advanced dementia should receive intensive medical care (6.5%).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Similar work led by Laura Hanson, MD, MPH, integrated a goals-of-care decision aid and care plan meetings in nursing homes; the study demonstrated more treatment planning and fewer hospital transfers for residents with advanced dementia [18].…”
Section: Innovative Approaches To Ensure Value From Endof-life Care Cmentioning
confidence: 80%